DETERMINANTS OF RESISTANCE IN BACTEROIDES FRAGILIS STRAIN BFR_KZ01 ISOLATED FROM A PATIENT WITH PERITONITIS IN KAZAKHSTAN - Kozhakhmetova, Saniya; Zholdybayeva, Elena V.; Tarlykov, Pavel; Atavliyeva, Sabina; Syzdykov, Tleuli; Daniyarov, Asset; Mukhtarova, Kymbat; Ramankulov, Yerlan (Elsevier Ltd, 2021)
Objectives: Bacteroides fragilis is one of the most important human anaerobic pathogens often found in various clinical infections. The purpose of this study was to determine the susceptibility of a B. fragilis clinical strain (BFR_KZ01) from Kazakhstan to the most commonly used anti-anaerobic drugs at the local level and to detect genes associated with resistance to these antibiotics. Methods: Species identification of the bacterial isolate was performed by matrix-assisted laser desorption/ionisation time-of-flight mass spectrometry (MALDI-TOF/MS) and 16S rRNA gene sequencing. Susceptibility to broad-spectrum antibiotics (metronidazole, meropenem, ciprofloxacin, clindamycin and tetracycline) most commonly used for the treatment of intra-abdominal infections (IAIs) was determined. Mass spectra groups essential for identifying cfiA-positive strains among clinical isolates were studied using ClinProTools 3.0.22 software. An Ion Torrent PGM™ platform was used for whole-genome sequencing (WGS) of the studied isolate. Results: The resulting WGS data of strain BFR_KZ01 was submitted to GenBank. In total, 5300 coding sequences (CDSs) and 69 RNA genes were determined. Analysis of the whole-genome data revealed that the studied strain harbours cfiA, nimB, tetQ and gyrA genes conferring resistance to key drugs used in treatment of the IAIs. MALDI-TOF/MS analysis assigned strain BFR_KZ01 to Group II (cfiA-positive); however, BFR_KZ01 was phenotypically sensitive to meropenem (mean MIC, 1.3 mg/L). Conclusion: Determinants of drug resistance in strain BFR_KZ01 were identified. It was revealed that B. fragilis strain BFR_KZ01 from Kazakhstan is multidrug-resistant since it carries nimB, tetQ and gyrA genes conferring resistance to metronidazole, tetracycline and ciprofloxacin.
Keywords: Type of access: Open Access; Bacteroides fragilis; Intra-abdominal infection; Peritonitis; Resistance gene; Whole-genome sequencing